Enhanced energy harvesting performance in lead-free multi-layer piezoelectric composites with a highly aligned pore structure. (February 2023) - Yan, Mingyang; Liu, Shengwen; Xu, Qianqian; Xiao, Zhida; Yuan, Xi; Zhou, Kechao; Zhang, Dou; Wang, Qingping; Bowen, Chris; Zhong, Junwen; Zhang, Yan
Abstract: The harvesting of mechanical energy from our living environment via piezoelectric energy harvesters to provide power for next generation wearable electronic devices and sensors has attracted significant interest in recent years. Among the range of available piezoelectric materials, porous piezoelectric ceramics exhibit potential for both sensing and energy harvesting applications due to their reduced relative permittivity and enhanced piezoelectric sensing and energy harvesting figures of merit. Despite these developments, the low output power density and the lack of optimized structural design continues to restrict their application. Here, to overcome these challenges, a lead-free multi-layer porous piezoelectric composite energy harvester with a highly aligned pore structure and three-dimensional intercalation electrodes is proposed, fabricated and characterized. The effect of material structure and multi-layer configuration of the porous piezoelectric ceramic on the dielectric properties, piezoelectric response and energy harvesting performance was investigated in detail. Since the relative permittivity is significantly reduced due to the introduction of aligned porosity within the multi-layer structure, the piezoelectric voltage coefficient, energy harvesting figure of merit and output power are greatly enhanced. The multi-layer porous piezoelectric composite energy harvester is shown to generate a maximum output current of 80 μA, with a peak power density of 209 μW cm −2, which is significantly higher than other porous piezoelectric materials reported to date. Moreover, the generated power can charge a 10 μF capacitor from 0 V to 4.0 V in 150 s. This work therefore provides a new strategy for the design and manufacture of porous piezoelectric materials for piezoelectric sensing and energy harvesting applications. Graphical Abstract: A flexible piezoelectric energy harvester based on lead-free multilayer piezoelectric composites with highly aligned pore structure and three-dimensional silver intercalation electrodes is designed and fabricated. The maximum output voltage and current generated by a four-layer porous piezoelectric energy harvester could reach 21 V and 80 μA, with a maximum output power density of 209 μW cm −2, which is capable of charging capacitors, illuminating commercial LEDs and supply power for electronic devices. ga1 Highlights: A lead-free multilayer piezoelectric composite energy harvester with aligned pore structure is designed and fabricated. The maximum output power density of a four-layer piezoelectric energy harvester could reach 209 μW cm −2 . The generated electricity can charge a 10 μF capacitor from 0 V to 4.0 V in 150 s. It is demonstrated to have the ability to charge capacitors, illuminate LED bulbs and power a stopwatch.